Status of Social Media Networks Utilization and their Impact of Prevalence of Extreme Groups’ Thoughts and Intellectual Terrorism among Youth - Badrakhan, Sawsan (Dirasat: Human and Social Sciences, 2021)
The study aims to identify the status of social media networks utilization and their Impact of the prevalence of extreme groups’ thougts and intellectual terrorism among youth and discuss if there were any significant statistical differences at ((α = 0.05) in the degree of the estimates of the study sample relating to the relationship between the prevalence of of extreme groups’ thougts and intellectual terrorism according to the variables of: gender, faculty and the academic year. A questionnaire including (28) items was designed and distributed among the study sample comprising (552) students selected from the University of Jordan and Ammman Al Ahliyyah University. The findings of the study revealed that the relation between the prevalence of of extreme groups’ thougts and intellectual terrorism was high. Moreover, there were no significant statistical differences in the sample answers that can be aributed to the variables of gender, faculty and the academic year. The study recommended to: enhance the national awareness among the community members, boost the attitude of loyalty and love of the nations towards their country anad stressed the need to face all thoughts and issues tackled on social media to avoid their negative impact on youth.